Spatial and temporal variability of coastal upwelling activity in Northwest Africa (1994–2022) - Chaimaa Jamal; Ahmed Makaoui; Melissa Chierici; Aziz Agouzouk; Hasnaa Nait Hammou; Adil Chair; Mohammed Idrissi; Omar Ettahiri; Fatima Zohra Bouthir; Bouya M'bengue; Samia Yousfi; Mouna Latifa Bouamrani (Scientific African, 2025)
Influenced by the Canary Current, the northwest African coast is one of the world's four major upwelling systems. This study is the first to investigate the latitudinal variability of upwelling activity along the Moroccan Atlantic coast, using a 28-year time series of in-situ data (1994–2022) analyzed on a seasonal scale. Five distinct zones were identified, each with specific oceanographic conditions. The Cape Cantin (32°30 N) and Cape Draa (28°30 N) regions show strong upwelling seasonality, with a peak in summer followed by relaxation in autumn. The North Atlantic Central Waters (NACW) strongly influences these areas. The Cape Boujdour (25°30 N) region exhibits the most active upwelling center, with near-permanent activity. Dakhla (23°30 N) is a water retention area influenced by the Cape Boujdour filament in autumn, while the Cape Blanc region (21°N) exhibits permanent upwelling activity throughout the year, acting as a frontal zone influenced by saltier NACW and South Atlantic Central Waters (SACW), which is less saline, phosphate-rich, and oxygen-depleted. Principal component analysis (PCA) confirmed the latitudinal and seasonal variability of upwelling. Cold, less saline, and phosphate-rich waters were more pronounced in summer across all zones. A relaxation of upwelling was observed in autumn, while the winter season showed an absence of upwelling, particularly in the northern zones (32°30N–28°30 N). Additionally, this study revealed a significant warming of surface waters in autumn 2015, and another warming event after 2019, coinciding with the Atlantic Niño phenomenon. These findings provide a valuable reference for understanding upwelling activity trends in this region.